2017
DOI: 10.1038/s41598-017-01472-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluorocarbon Thin Films Fabricated using Carbon Nanotube/Polytetrafluoroethylene Composite Polymer Targets via Mid-Frequency Sputtering

Abstract: Carbon nanotube/polytetrafluoroethylene composite polymer targets are proposed for use in the fabrication of fluorocarbon thin films using the mid-frequency sputtering process. Fluorocarbon thin films deposited using carbon nanotube/polytetrafluoroethylene composite targets exhibit an amorphous phase with a smooth surface and show a high water contact angle, optical transmittance, and surface hardness. X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy studies reveal that as the carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 73 publications
1
39
0
Order By: Relevance
“…Coating technologies are strongly related to dramatic changes of surface wetting behavior and thus continuously investigated by many researchers 36 41 . Composite coatings are also effective techniques for accumulating multiple functions on substrate surface.…”
Section: Introductionmentioning
confidence: 99%
“…Coating technologies are strongly related to dramatic changes of surface wetting behavior and thus continuously investigated by many researchers 36 41 . Composite coatings are also effective techniques for accumulating multiple functions on substrate surface.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6a shows the normalized C 1s core-level XPS spectra of the Cu/PPFC nanocomposite thin films prepared by RF sputtering of the Cu/PTFE composite target. The C 1s spectra exhibit broad Gaussian deconvolution peaks that have the following customary assignments for a fluorocarbon thin film: 294.0 eV (CF 3 ), 292.0 eV (CF 2 ), 289.8 eV (CF), 287.5 eV (C-CF n ), and an additional C=O peak at 288.6 eV owing to binding with oxygen [16,31,34]. The intensity of the CF 2 bond, which is typical in a fluorocarbon thin film, is decreased owing to the low fluorine bonding ratio and high carbon bonding ratio in the thin film with increasing Cu content.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, our group found that a plasma polymer fluorocarbon (PPFC) thin film prepared using a carbon nanotube (CNT)/PTFE composite sputtering target exhibited diverse physical properties depending on the content of the CNT. In addition, it has been reported that CNT, when added to a composite target, imparts conductivity; hence, sputtering is also possible using a mid-range frequency (MF) power source [31]. Taking our previous study forward, in this study, a Cu/PTFE composite target for sputtering was first introduced for fabricating a Cu/PPFC nanocomposite thin film by uniformly dispersing Cu metal powder in PTFE powder and pressing at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…| 3 of 9 CF 2 , CF 3 , and C-CF x bonds in the plasma polymer. [45] Figure 2 shows the deconvolution of C 1s peak for three plasma polymer films deposited in Ar, Ar/N 2 , and Ar/ N 2 :C 2 H 2 plasma. Adding nitrogen leads to nitrogen incorporation in the form of CN bonds, which in turn leads to a higher amount of CF 2 in the polymer film (see Figure 2a,b), similarly to the what has been reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%